Water intake and wastage during the growing-finishing period of immunocastrated and surgically castrated pigs - Da Costa Mendes Muniz H. (2021)
© 2021 CSIRO.Context: An adequate management of water use is essential in agricultural systems, including pig farming. Reducing the water footprint is important to preserve this natural resource, although there is limited qualitative information about water intake and water intake behaviour, especially in immunocastrated pigs. Aim: The objective of this study was to compare water disappearance, and estimate wasted water and water intake behaviour for immunocastrated and surgically castrated male pigs. Methods: Twenty-four surgically castrated male pigs and 24 entire male pigs submitted to immunocastration were used, with an average initial weight of 29.3 kg (±1.9 kg) and an age of 75 days. The pigs were housed in a growing-finishing facility with 24 pens and two animals per pen; each pen was equipped with a semi-automatic feeder and a bite-ball drinker with a water meter. The disappearance of water was measured by collecting the values of the water meters on a daily basis, and the water intake behaviour was determined by collecting the values of the water meters per hour. Water input and output values were estimated, and wasted water was calculated by subtracting the input from the output value. Key results: The weekly average water disappearance for surgically castrated males was higher (P < 0.05) than that for immunocastrated males, except in the last 2 weeks of the experimental period; the same was observed when expressed based on weight. Castrated animals also wasted 21.4% more water than immunocastrated animals. Regarding the water consumption profile, there were no differences between the two groups; water consumption was higher in the afternoon. The lower water disappearance in immunocastrated pigs was due to the increase in feed intake after the second dose of the immunocastration vaccine and to the lower amounts of waste because of less aggressive behaviour. Conclusion: Immunocastrated male pigs have a smaller water footprint, but a similar water intake behaviour compared with surgically castrated animals. Implications: Knowledge of the profile of water intake and a way to estimate water waste allows more efficient and sustainable management of water resources in pig production systems.